Strategic information transmission and stochastic orders - Dezsö Szalay (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2012)
I develop new results on uniqueness and comparative statics of equilibria in the Crawford and Sobel (1982) strategic information transmission game. For a class of utility functions, I demonstrate that logconcavity of the density implies uniqueness of equilibria inducing a given number of Receiver actions. I provide comparative statics results with respect to the distribution of types for distributions that are comparable in the likelihood ratio order, implying, e.g., that advice from a better informed Sender induces the Receiver to choose actions that are more spread out.
urn:nbn:de:bvb:19-epub-14011-6
Keywords: D82; 330; strategic information transmission; cheap talk; uniqueness; comparative statics; logconcavity; likelihood ratio order; Informationsverhalten; Informationsverbreitung; Spieltheorie; Gleichgewicht; Theorie